The use of Higher Plants as Bio-Indicators of Environmental Pollution – A New Approach for Toxicity Screening in Albania - Dizdari, Anila Mesi; Kopliku, Ditika; Golemi, Suzana (Richtmann Publishing, 2012)
The purpose of this paper was to give an information review of some higher plants as: Allium cepa, Tradescantia genus, Viciafaba, Pisum sativum, Zea mays, Nicotiana tabacum, Lycopersicon esculentum, Lemna minor, etc., which can be properly used as bioindicatorsfor assessing and predicting pollution toxicity and environmental changes in Albania. Plants, apart their structure andmetabolic priorities, can give essential information and data about the potential toxicity of substances, even when exposed in short termand low concentrations. They offer advantages against animals as bioindicators, because of the low cultivation cost, easier maintenance,ethically and esthetically acceptable handle. The plant assays can: be carried out under a wide range of environmental conditions, giveaccess to the cito/genotoxic potential of known/unknown simple substances or even complex mixtures (present in water, soil and air) andhave shown correlations with cytogenetic assays in mammals. In many sensitive species chemicals induce specific morphological andphyiological changes. Sometimes the same plant species may act as both indicator and accumulator for a special pollutant. Plants aredirect recipients of agro-toxics and therefore important material for environmental monitoring of places affected by such pollutants. Allabove mentioned higher plants are part of Albanian wild and cultivated vegetation, so as a conclusion plant toxicity screening methodscan provide a new approach, potentially applicable in Albania as a developing country, where chemical pollution monitoring is reallyexpensive. Additionally simple plant bio-tests can be included in Albanian curricula.